Análisis bioinformático de la inmunogenicidad de la proteína PE_PGRS18 de Mycobacterium tuberculosis - Jiménez Ruiz, Eva Nelida (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The PE and PPE proteins of M. tuberculosis have proven to be potent antigens that are recognized by B and T cells. Our working group found that the pe_pgrs18 gene of M. tuberculosis strains of Michoacán was one of the most polymorphic. It is important to look for peptides in the PE_PGRS18 protein that bind to CMH class I and II molecules, to analyze whether this gene is capable of inducing a cellular immune response (adaptive immune response) and whether the study protein can interact with the host’s TLRs 2 and 4 (innate immune response). These peptides could be tested in the future for inclusion in a tuberculosis vaccine or for early identification of the disease. For this, 46 sequences of the pe_pgrs18 gene from M. tuberculosis strains from Michoacan and Queretaro of were analyzed. Mega, PredictProtein, Signal –IP, Computer pl / Mw, Pryre 2, Prism, NetMHCpan, NetMHCIIpan and Galaxypepdock servers were used. Results. The PE_PGRS18 protein has loops (43.11%), beta sheets (40.04%), alpha helices (16.85%), a signal sequence at position 36-56 aa, an isoelectric point of 4.27, a molecular weight of 42074.79 Da and 17 protein-binding regions. The protein is membrane integral; 78.56% is hydrophobic and lacks disulfide bonds. 5,114 epitopes of high affinity to CD8 + T lymphocytes were identified, the A_6802 allele binds to a greater number of epitopes, in addition to 995 high affinity alleles to CD4 + T lymphocytes, the DRB_0407 allele binds to a greater number of epitopes. 332 mutations were identified, of which 244 stimulate and 88 evade the immune response mediated by CD4 + and CD8 + T cells. No direct interaction of the PE_PGRS18 protein was observed with the TLR2 and TLR4 receptors.

Las proteínas PE y PPE de M. tuberculosis han demostrado ser potentes antígenos que son reconocidos por células B y T. Nuestro grupo de trabajo encontró que el gen pe_pgrs18 de cepas de M. tuberculosis de Michoacán era de los más polimórficos. Es importante buscar péptidos en la proteína PE_PGRS18 que se unan a moléculas del CMH clase I y II, para analizar si este gen es capaz de inducir una respuesta inmune celular (respuesta inmune adaptativa) y si la proteína de estudio puede interaccionar con los TLRs 2 y 4 del hospedero (respuesta inmune innata). Estos péptidos podrían probarse a futuro para su inclusión en una vacuna contra la tuberculosis o para la identificación temprana de la enfermedad. Para ello se analizaron 46 secuencias del gen pe_pgrs18 de cepas Michoacanas y de Queretaro de M. tuberculosis. Se utilizaron los servidores Mega, PredictProtein, Signal –IP, Computer pl/Mw, Pryre 2, Prism, NetMHCpan, NetMHCIIpan y Galaxypepdock. Resultados. La proteína PE_PGRS18 tiene loops (43.11%), laminas beta (40.04%), hélices alfa (16.85 %), una secuencia señal en la posición 36-56 aa, un punto isoeléctrico de 4.27, un peso molecular de 42074.79 Da y 17 regiones de unión a proteínas. La proteína es integral de membrana, un 78.56% es hidrofóbica y carece de enlaces disulfuro. Se identificaron 5,114 epítopes de alta afinidad a linfocitos T CD8+; además de 995 alelos de alta afinidad a linfocitos T CD4+. Se identificaron 332 mutaciones de las cuales 244 estimulan y 88 evaden la respuesta inmune mediada por los linfocitos T CD4+ y CD8+. No se observó una interacción directa de la proteína PE_PGRS18 con los receptores TLR2 y TLR4.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2020-0609; Inmunogenicidad; Bioinformática; Mutación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3021